Factors that affect Malaysian Ringgit currency (1995 - 2009) / Norisma Wahida Ab Wahab - Ab Wahab, Norisma Wahida (Faculty of Business and Management, 2010)
This paper attempts to identify the factors that affect the Malaysian Ringgit (MYR)during Year 1995-2009 in comparison with those of the Malaysian experience. It consists three independent variable which is inflation rate, economic growth and also investment where come from balance of payment of Malaysia. This paper also studies the relationship of the three independent variables with MYR. Using SPSS and DataStream as the way to find the data, the paper concludes that the some of the independent variable have significant relationship with the studies. The Malaysian economy faced major constraints represented in financial crises, slowdown in the global demand for electronics, fall in investment rate, high unemployment, and public debt, yet was able to continue recovering the economic performance after downturns with both its fiscal and monetary policies supporting its economic activity. As the paper are only use data for 15 years, it is recommended to use the data which is more than 20 years to find it significant level for the independent variables.